Capecitabine for treating head and neck cancer. (2nd July 2016) - Iqbal, Hassan; Pan, Quintin
ABSTRACT: Introduction : With an increasing incidence, over half a million cases of head and neck cancer (HNC) are diagnosed annually worldwide. Various chemotherapeutic agents are utilized to achieve adequate locoregional control. Cisplatin, fluorouracil (FU), and taxanes are often used to treat HNC but these regimens have shown high toxicity and poor patient compliance. Capecitabine is an orally administered prodrug that is preferentially converted to FU in tumor cells in comparison to normal cells. Area covered : In this review, the authors evaluate the role of capecitabine in radical and palliative settings either alone or in combination with other chemotherapeutic drugs in the management of HNC. In addition, metabolic conversion, pharmacokinetics, pharmacodynamics, and toxicity profile of capecitabine are discussed. Expert opinion : Various phase II trials conducted on capecitabine in the management of recurrent HNC have shown comparable results and tolerable toxic effects especially in pre-treated fragile patients. Capecitabine, used in induction or concurrent settings in the radical management of locoregionally advanced HNC, have also shown promising results. Randomized trials are needed to validate the role of capecitabine in the management of HNC.